Narrative Representation of Violence-Induced Trauma Under Israeli Occupation: A.J. Greimas’s Semiotic Analysis of Tafṣīl Ṡānawī - Amanda Siva Saepuloh; Rohanda Rohanda; Irfan Adriadi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
rauma resulting from violence often cannot be expressed directly in literary texts but instead emerges symbolically, hidden beneath the narrative. Nevertheless, through literature, Palestinian writers strive to record histories that are often overlooked by official narratives. This study aims to uncover the representation of trauma in Adania Shibli’s novel Tafṣīl Ṡānawī through A.J. Greimas’s narrative semiotics. The novel serves as a literary representation that reveals Zionist violence and its accompanying trauma within the context of Israel’s occupation of Palestine. Employing a qualitative-descriptive method with textual documentation, this research analyzes the actantial structure, spatial and temporal isotopies, and the inner structure through the semiotic square. The findings indicate that trauma in the novel is not only explicitly narrated but also symbolically manifested through spatial and temporal tensions and the interplay of actants within the story. Violence, the erasure of traces of violence, resistance, and the silencing of the narrator are represented within interlocking semiotic relations. This study demonstrates that trauma in the text is structural and transgenerational, functioning as a symbolic field of resistance against power exercised through cultural violence. The findings further suggest that literary works can function as archives of collective memory, open critical spaces for interpreting historical wounds, and underscore the importance of semiotic perspectives in reconstructing trauma that is not explicitly depicted in modern Arabic literature.